(untitled) (San Francisco, California, 1964)
Based on the premise that today's college students must write effectively about what they have read, this textbook offers readings alongside the usual advice about good writing skills. Readers are asked to respond to the various readings, ranging from humorous essays to political arguments from liberal and conservative commentators.
Keywords: English language,Technical writing; Rhetoric